Diversity of ABO blood groups, ethnic groups, and medical histories of university students in Indonesia - PUJI RIANTI; ZAHRA RODLIYATAM MARDLIYAH; DEDY DURYADI SOLIHIN (Jurnal Natural, 2023)
. Blood group systems are heritable characteristics controlled by multiple alleles that determine the presence of antigens A, B, or the absence of antigens (O). These systems are crucial in categorizing humans' four main blood groups. ABO blood groups have been identified to correlate with evolution, migration, local adaptations, dietary patterns, and human diseases. Unfortunately, this knowledge is poorly known in Indonesia. Therefore, we initiate this study to record university students' blood groups' diversity through the frequency of ABO alleles, ethnicities, and medical histories through questionnaires. The data analysis involved the responses of 992 students aged 17 to 23 from IPB University. The ABO estimator version 17.3 and Program R ver. 3.6.3 were utilized for data analysis, with the sample size determined using the Slovin formula. Our analysis revealed allele frequencies of 0.19 for IA, 0.20 for IB, and 0.61 for IO. The O blood group exhibited the highest prevalence, while the AB blood group was the rarest. Individuals with the O blood group identified as Javanese and Sundanese were more likely to have histories related to typhoid/typhoid symptoms and dengue fever. Individuals with O and B blood groups from the Sundanese population experienced allergies. In contrast, those with blood group B from the Javanese population were more prone to gastric ulcers and asthma. There are no significant differences between ethnicities for each illness record except asthma. All ABO blood groups for each illness record show significant differences with a weak correlation between the blood groups and type of illness.